2017
DOI: 10.5194/acp-2017-510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nepal Ambient Monitoring and Source Testing Experiment (NAMaSTE): Emissions of particulate matter from wood and dung cooking fires, garbage and crop residue burning, brick kilns, and other sources

Abstract: Abstract.The Nepal Ambient Monitoring and Source Testing Experiment (NAMaSTE) characterized widespread and 20 under-sampled combustion sources common to South Asia, including brick kilns, garbage burning, diesel and gasoline generators, diesel groundwater pumps, idling motorcycles, traditional and modern cooking stoves and fires, crop residue burning, and a heating fire. Fuel-based emission factors (EF; with units of pollutant mass emitted per kg of fuel combusted) were determined for fine particulate matter (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Christian et al [29] found emission factors of OC=5.3 (±4.9) and BC=0.65 (±0.27) g kg −1 burned. These emission factors are within the reported range of 0.04-9.97 g BC kg −1 burned from recent measurements of trash burning in Nepal where some samples were enriched for specific compositions of plastic and foil [31], but lower than the reported range of 8.4-73.9 g OC kg −1 burned. MSW emissions can vary significantly and have high uncertainties due to the composition of the waste and stage of combustion [13,32].…”
Section: Msw and Dung Cake Burn Inventories To Aermod Dispersion Modesupporting
confidence: 85%
“…Christian et al [29] found emission factors of OC=5.3 (±4.9) and BC=0.65 (±0.27) g kg −1 burned. These emission factors are within the reported range of 0.04-9.97 g BC kg −1 burned from recent measurements of trash burning in Nepal where some samples were enriched for specific compositions of plastic and foil [31], but lower than the reported range of 8.4-73.9 g OC kg −1 burned. MSW emissions can vary significantly and have high uncertainties due to the composition of the waste and stage of combustion [13,32].…”
Section: Msw and Dung Cake Burn Inventories To Aermod Dispersion Modesupporting
confidence: 85%
“…Both the "zig-zag" and clamp kilns measured by Stockwell et al (2016) in Nepal also used coal as fuel. Jayarathne et al (2017) recently reported the particle-phase results of the same kilns measured by Stockwell et al (2016). Of these studies, Stockwell et al (2016) and Christian et al (2010) report fuel-based energy factors whereas Rajarathnam et al (2014) and Weyant et al (2014) report energy-based emission factors, allowing a proper inter-comparison with our results.…”
Section: Comparison With Other Studies 30mentioning
confidence: 90%
“…5,17 Soot, polycyclic aromatic hydrocarbons (PAHs), transition metals and endotoxins have low atmospheric abundance, but are capable of contributing adverse health effects. 5,17,25,27,[50][51][52] However, certain emissions from particular sources like exhaust smoke of plastic and tire burning, welding, coke-oven, aluminum smelting, diesel and gasoline engines contain harmful species such as PAHs and trace metals. [53][54][55][56] Therefore, the chemical composition of PM is expected to be an important determinant in its health outcome and useful for setting up occupational exposure limits and human exposure studies.…”
Section: Effects On Human Healthmentioning
confidence: 99%
“…[94][95][96][97][98][99][100] However, up-todate only few studies have focused on comprehensive measurements of both gas-phase and particulate-phase emissions. 50,96,98,100 Further, EFs of biomass burning PM is highly dependent on fuel type (soft wood, hard wood, grass, organic soil), fuel moisture content and burning condition (flaming vs smoldering). 94,98,101 Thus, more studies are needed to understand the emission variation of PM under different burning conditions.…”
Section: Biomass Burning Aerosolmentioning
confidence: 99%
See 1 more Smart Citation